Programmes de développement des compétences sociales et d’insertion professionnelle chez les etudiant.e.s : efficacité et limites - Hernandez, Lucie (L'orientation scolaire et professionnelle, 2016)
The current problems relating to the professional integration of young people led researchers and practitioners to focus on complementary skills to professional skills: social skills. In this context, programs for students aimed at developing these skills have been created. This article presents eight of these programs and for each one, the specific objectives, contents (pedagogies, targeted social skills, and duration), assessments conducted and results are described, compared and analyzed. In highlighting the criteria of effectiveness of these programs and their limitations, the aim is to reveal findings and useful proposals for action for the implementation of future programs.